Caracterização geológica e tecnológica do arenito da formação cabeças (Pedra mourisca) de Castelo do Piauí - PI. - Freitas Filho, Agnaldo Francisco de (2018)
The present work presents the sandstones of the head formation of the Parnaiba-Pi basin, known commercially as Yellow, Black and Multicor, come from the same mining front located in the municipality of Castelo do Piauí / Pi. In order to evaluate its qualities for application as ornamental rock, petrophysical tests, thermal conductivity, physical and physical-mechanical indexes based on ABNT norms were carried out, the rocks analyzed have a similar mineral composition, being formed essentially by quartz, plagioclase, muscovite. Petrografically corresponds to immature mineral sandstones varying from very thick to thick, high degree of porosity, mineral alteration ranging from incipient to moderate and predominant concave-convex mineral contacts. In general, the results obtained in the technological characterization tests indicate that the three types of sandstone studied do not meet the parameters suggested by the current norms. The physical indices presented values ​​outside the average for Brazilian siliciclastic rocks, namely, apparent specific mass, porosity and water absorption, respectively, with 2344 kg / m³, 3.38% and 7.93% of NBR 15,845-2 (ABNT- 2015). The values ​​of uniaxial compression strength were only one of the samples that managed to exceed the average for Brazilian siliciclastic rocks and also within the limits of NBR 15.845-5 (ABNT-2015). With respect to the three point flexural test, the rock exhibited value, well above the average for Brazilian siliciclastic rocks and NBR 15.845-6 (ABNT-2015). The behavior of the samples when subjected to AMSLER wear, provided a performance that was well above the wear for a 1000m course, above the average for Brazilian siliciclastic rocks. The rock petrophysics studied, such as porosity, density and wave propagation velocity, which are of particular importance in ornamental rock planning, are mostly based on the following properties: porosity, grain density, wave propagation velocity ultrasound (VP and VS). The tests to obtain these parameters are often performed on collected cylindrical samples. According to the results obtained in this research, it is verified that the sandstone types Yellow, Black, and Multicor can be used as ornamental and cladding rock, with caveats that the norms used do not specify for the material.